INSIGHT INTO TROPICAL HUMAN INFECTIOUS DISEASES: AN UPDATE - Poopathi, Subbiah; -, Abdha (African Journal of Infectious Diseases (AJID), 2008)
Knowledge on infectious diseases encompasses a vast and constantly changing arena, and consistent research work is imperative to understand and combat the new problems resulting from emerging infectious diseases. Public health workers and epidemiologists aim at lowering morbidity and mortality due to diseases by preventing infections. For the rapidly expanding majority of the world’s population, who live in the largely tropical areas of Africa, Asia and Latin America, the greatest threats to health remain tropical infectious diseases. Emerging infectious diseases are new, emerging or drug-resistant infections, whose incidence in humans may increase in the near future. With rapidly increasing international travel, the globalization and industrialization of food supply and exploding populations, infectious diseases pose unprecedented threats around the globe. Thus the imperative need is to promptly recognize, isolate and appropriately manage tropical infectious diseases. This review paper has attempted to provide the much needed insight into the different aspects of the major tropical infectious diseases affecting humans throughout the world.